(untitled) (Journal of the College of Basic Education, 2022)
This research included a study of the genetic frequencies of ABO and Rh blood groups for a sample from the city of Baghdad consisting of (3000) individuals (1140) males and (1860) females as a representative sample of the city on both sides of Karkh and Rusafa.